Browne, Spain’s Civil War - Kern, Robert (Teaching History: A Journal of Methods, 1998)
The Spanish Civil War, once famed but now relatively forgotten at the end of the twentieth century, still attracts coverage. Harry Browne, a British professor of Spanish history and literature, has prepared for Longman’ s Seminar Series in History a narrative historical text of slightly over a hundred pages, accompanied by 27 pages of translated documents on key episodes and actors in the civil war. There is also a short section identifying key personalities, a glossary, and a short bibliography.